Classification of analogies as a methodological framework for use in instruction in physics - Baisalova, K.N.; Lombardi, Guido; Sautbekov, S.S. (Recent Contributions to Physics, 2023)
In the article, the author provides a detailed description of the methodology used to collect and analyze research data, and the process of developing a classification system. The main part of this study is based on the results of a survey of physics teachers. The author also showed that the data collected during the survey were qualitatively analyzed using thematic analysis, and a comprehensive system of classification of analogies in physical education was developed. It is described that analogies in teaching physics can be divided into two main groups. These are subjective and intersubject analogies. That is, the development of a comprehensive system of classification of analogies that can be used in physics education is being considered in detail. The use of analogies is studied as a means to improve students’ understanding of abstract scientific concepts, in particular, in the context of electromagnetism. The research uses a methodology for analyzing scientific literature based on various sources to identify and evaluate different approaches to analog thinking in physics education. The results of the study demonstrate that the analogy classification system can greatly simplify the explanation of complex scientific concepts, providing teachers with a valuable tool for improving pedagogical practices. In addition, the proposed classification system offers a framework for developing new analogies and improving existing ones, contributing to the development of more effective teaching methods. In general, the study emphasizes the importance of analogical thinking in physics education and offers practical findings that can be applied in the development of educational materials in various fields based on the use of analogies.